Scalar controversies in oil and gas governance: Perspectives on who should regulate the oil and gas industry from policy actors in Colorado and Utah. Issue 1 (January 2019) - Mayer, Adam
Highlights: Survey of local policy actors in the Mountain West region of the U.S. Policy actors asked to report their scalar preferences for oil and gas regulations. Generally, local policy actors endorse local control. There are significant differences between Republicans and non-Republican policy actors. Abstract: In the U.S., the current regulatory regime for unconventional oil and gas development is extremely contested, with controversial exemptions buried in federal law and significant state-local conflict. Hence, the question of the appropriate scale of governance (e.g. federal, state, or local) for oil and gas development is unsettled. In this analysis, we consider the views of local policy actors in the western states of Utah and Colorado. We ask how factors such as the perceived importance of the industry and local economic conditions influence scalar preferences. Results imply that local policy actors tend to endorse local control and are generally not supportive of federal exemptions.